Bunuel wrote:

Does \(\frac{x}{n}(s^2 + n^2 + t^2) = xn + yt + zs\)?

(1) xs = zn

(2) xt = yn

Clearly, individually the statements are not sufficient

and best way to start is by simplifying the equationlets see combined

\(LHS=\frac{x}{n}(s^2 + n^2 + t^2)=\frac{xs^2}{n}+\frac{xn^2}{n}+\frac{xt^2}{n} =\frac{xs*s}{n}+xn+\frac{xt*t}{n}\)

substitute the values xs=zn and xt=yn

\(\frac{zn*s}{n}+xn+\frac{yn*t}{n}=zs+xn+yt=RHS\)

so ans is YES

suff

C

_________________

1) Absolute modulus : http://gmatclub.com/forum/absolute-modulus-a-better-understanding-210849.html#p1622372

2)Combination of similar and dissimilar things : http://gmatclub.com/forum/topic215915.html

3) effects of arithmetic operations : https://gmatclub.com/forum/effects-of-arithmetic-operations-on-fractions-269413.html

GMAT online Tutor